The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/2675-2824069.21008cep
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Literacy, formal education, and governance: A diagnosis of Brazilian school curricula as a strategy to guide actions during the Ocean Decade and beyond

Abstract: Ocean Literacy (OL) was proposed by UNESCO as a goal for the Decade of Ocean Science for Sustainable Development (Ocean Decade) aiming to (1) increase understanding of the importance of the ocean, (2) significantly influence communication on related subjects, and (3) facilitate informed and responsible decision-making about the ocean and its resources. Formal education is essential to expand the reach of OL, providing people with tools to engage in coastal and marine issues consciously and knowingly. To this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…The significance of incorporating OL principles and concepts into the school curriculum to enhance societal understanding and consciousness of marine environmental issues has been widely acknowledged (Guest et al, 2015; Payne & Zimmerman, 2010; Santoro, Santin, Scowcroft, Fauville & Tuddenham, 2017; United Nations, 2018). Thus, the analysis of school curricula is the first initiative so that the potential and challenges of including these contents are achieved (Pazoto et al, 2021). Despite the acknowledged importance of OL, there has been a paucity of research examining its presence in formal education curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of incorporating OL principles and concepts into the school curriculum to enhance societal understanding and consciousness of marine environmental issues has been widely acknowledged (Guest et al, 2015; Payne & Zimmerman, 2010; Santoro, Santin, Scowcroft, Fauville & Tuddenham, 2017; United Nations, 2018). Thus, the analysis of school curricula is the first initiative so that the potential and challenges of including these contents are achieved (Pazoto et al, 2021). Despite the acknowledged importance of OL, there has been a paucity of research examining its presence in formal education curricula.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the acknowledged importance of OL, there has been a paucity of research examining its presence in formal education curricula. Two prior studies conducted in Brazil analysed national and regional curriculum documents at the elementary school level, with one study identifying only a small fraction of content related to ocean and marine themes (Pazoto et al, 2021), and the other concluding that only five of the seven OL principles and 14 concepts were represented in the analysed documents (Pazoto et al, 2022). In contrast, our study found that the Brazilian secondary education curriculum incorporates the vast majority of OL principles and concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Ocean Literacy, which also guided our activities, already existed in the United States as a movement to incorporate Ocean Sciences-related topics into formal education in the early 2000s [Pazoto et al 2022]. However, Ocean Literacy was only adopted in Brazil in 2019, following the Portuguese release of the book Ocean Literacy for All: A toolkit by UNESCO [Pazoto et al 2021], which discusses the 7 principles that govern the movement. Today, Ocean Literacy is promoted as a goal for achieving the behavioral change expected for the Ocean Decade [Unesco 2021].…”
Section: Discussionmentioning
confidence: 99%
“…Topics of ocean literacy and marine science issues are underrepresented areas in the school curriculum and textbooks worldwide (Mokos et al, 2020;Mogias et al, 2021;Mogias et al, 2022). In Latin America, Brazil is taking the first steps to analyze and integrate marine content into the school curriculum, given the international context of the Decade of Oceanic Sciences (Pazoto et al, 2021). In Chile, the only review of marine content in the school curriculum is that of Fanta ( 2021), which analyzed the curriculum bases from preschool to high school, finding the words "sea" and "ocean" only 16 times in the primary and secondary educational cycle, highlighting the weakness of school marine education in Chile.…”
Section: School Science Education In Chilementioning
confidence: 99%